1999
DOI: 10.1046/j.1365-2443.1999.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in nuclear morphology during apoptosis correlate with vimentin cleavage by different caspases located either upstream or downstream of Bcl‐2 action

Abstract: Background: Upon Fas stimulation, procaspase-8 is recruited to the death-inducing signalling complex where autoactivation of caspase-8 occurs. Active caspase-8 can directly activate downstream caspases (e.g. caspase-3, 6, and 7) for the execution of apoptosis (mitochondria-independent pathway), while caspase-8 can also lead to executioner caspase activation through mitochondrial damage (mitochondria-dependent pathway). Caspase activation results in the dismantling of intracellular structure through specific pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 55 publications
4
79
0
2
Order By: Relevance
“…Y. Eguchi and Y. Tsujimoto (Osaka University, Osaka, Japan). Apoptosis induction was performed as described previously (9). Briefly, cells (5 ϫ 10 5 cells/ml) were treated with 200 ng/ml anti-Fas monoclonal antibody (clone CH-11, Medical and Biological Laboratories, Nagoya, Japan) and 20 g/ml cycloheximide (Calbiochem) or 1 M staurosporine (Calbiochem).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Y. Eguchi and Y. Tsujimoto (Osaka University, Osaka, Japan). Apoptosis induction was performed as described previously (9). Briefly, cells (5 ϫ 10 5 cells/ml) were treated with 200 ng/ml anti-Fas monoclonal antibody (clone CH-11, Medical and Biological Laboratories, Nagoya, Japan) and 20 g/ml cycloheximide (Calbiochem) or 1 M staurosporine (Calbiochem).…”
Section: Methodsmentioning
confidence: 99%
“…Several lines of evidence, including the order of the multiple cleavages on the vimentin polypeptide, indicate that the initial cut is made at Asp 259 by an initiator caspase, probably either caspase-8 or caspase-9. The Asp 259 cleavage occurs in the absence of the activities of effector caspases (9). The sequence around the cleavage site (Ile-Asp-Val-Asp 259 -Val) matches the sequence preferences of both caspases-8 and -9 in having an aliphatic amino acid residue at the P4 position (10).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…In support of this, we found that a majority of the reactive astrocytes expressing vimentin also were positive for cleaved caspase-3. Vimentin is specifically cleaved by caspase-3, irreversibly dismantling intermediate filaments (Byun et al, 2001), which may impact the integrity and dynamics of intracellular structures (Morishima, 1999). Similarly, the GFAP sequence contains a single caspase consensus sequence, DLTD 266 , based on the general tetrapeptide motif DXXD recognized by caspases, and the antibody CCP-GFAP used in this study was synthesized to the downstream neoepitope that would be generated after caspase cleavage of full length GFAP (Mouser et al, 2006).…”
Section: Presence Of Caspase-cleaved Gfapmentioning
confidence: 99%